Mutations in JARID1C are associated with X-linked mental retardation, short stature and hyperreflexia. Issue 12 (12th August 2008) - Abidi, F E; Holloway, L; Moore, C A; Weaver, D D; Simensen, R J; Stevenson, R E; Rogers, R C; Schwartz, C E
Abstract : Background: Mutations in the JARID1C (Jumonji AT-rich interactive domain 1C) gene were recently associated with X-linked mental retardation (XLMR). Mutations in this gene are reported to be one of the relatively more common causes of XLMR with a frequency of approximately 3% in males with proven or probable XLMR. The JARID1C protein functions as a histone 3 lysine 4 (H3K4) demethylase and is involved in the demethylation of H3K4me3 and H3K4me2. Methods: Mutation analysis of the JARID1C gene was conducted in the following cohorts: probands from 23 XLMR families linked to Xp11.2, 92 males with mental retardation and short stature, and 172 probands from small XLMR families with no linkage information. Results: Four novel mutations consisting of two missense mutations, p.A77T and p.V504M, and two frame shift mutations, p.E468fsX2 and p.R1481fsX9, were identified in males with mental retardation. Two of the mutations, p.V504M and p.E468fsX2, are located in the JmjC domain of the JARID1C gene where no previous mutations have been reported. Additional studies showed that the missense mutation, p.V504M, was a de novo event on the grandpaternal X chromosome of the family. Clinical findings of the nine affected males from the four different families included mental retardation (100%), short stature (55%), hyperreflexia (78%), seizures (33%) and aggressive behaviour (44%). The degree of mental retardation consisted of mild (25%), moderate (12%) and severe (63%). Conclusion: Based on the clinical observations, male patients with mental retardation, short stature and hyperreflexia should be considered candidates for mutations in the JARID1C gene.